Changes in morbidity over time: Evidence from Europe - Dörte Heger; Ingo W.K. Kolodziej (RWI - Leibniz-Institut für Wirtschaftsforschung, 2016)
The elderly are the main beneficiaries of recent gains in life expectancy in the EU. Whether the additional life time is spent in good or in poor health will drastically influence the development of health care costs as morbidity status rather than age per se determines an individual's need for health care services. However, empirical evidence on whether the prolonged lifespan is associated with a compression or an extension of morbidity is still sparse and inconclusive. In this paper, we analyse disability levels in the population 50+ in Europe by age and by proximity to death over time using longitudinal data from the Survey of Health, Ageing, and Retirement in Europe (SHARE). We find that disability levels in Europe have increased due to population ageing and an increase in the prevalence of diseases. The disabling effect of health conditions remained constant over time.
Keywords: I10; J11; J14; 330; ageing; compression of morbidity; Blinder-Oaxaca decomposition